Pengaruh strategi green marketing melalui pendekatan marketing mix terhadap keputusan pembelian serta loyalitas - Raynald Yosua Mamahit; Suharno Suharno; Tetra Hidayati (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The analysis model used in this research is using Path Analysis (Path Analysis). The results showed that the variable equation green product, price, promotion, distribution positive influence on purchase decision. This means that any increase in green product, price, promotion, distribution will have an impact on the increase in purchase decision, the second equation it can be concluded that the purchase decision variable positive effect on loyalty. This means that any increase in the purchase decision will have an impact on the improvement of product loyalty The Body Shop in the Big Mall Samarinda.The coefficient of R (correlation) indicates that there is a strong relationship of variable green product, price, promotion, and distribution of the product purchasing decisions of The Body Shop in the Big Mall Samarinda. The coefficient of R (correlation) indicates that there is a strong relationship of variable purchase decisions loyalty product of The Body Shop in the Big Mall Samarinda.Partially green products and distribution significantly influence purchasing decisions. While the sale price and not significant effect on purchasing decisions and significantly influence the purchasing decisions of products of The Body Shop in the Big Mall Samarinda